Examining the Contribution of Baduy Ethnomathematics to Enhancing Non-Routine Problem-Solving Skills - Nawal Ika Susanti; Moh. Abdul Qohar (SIMFONI: Jurnal Sains dan Sosial Multidisipliner, 2025)
This study aims to synthesize the contribution of Baduy ethnomathematics in enhancing students’ non-routine problem-solving skills. The research is motivated by the gap between formal mathematics learning, which often emphasizes routine procedures, and the need to develop higher-order thinking skills (HOTS). The method employed was a Systematic Literature Review (SLR) using the PRISMA protocol, covering 20 primary studies published between 2020 and 2025. The analysis focused on identifying mathematical concepts embedded in Baduy cultural practices, models of classroom implementation, and their relevance to Polya’s problem-solving heuristics. The findings reveal three major thematic clusters: spatial geometry and transformation (ratios in Sulah Nyanda houses, symmetry in weaving), communal arithmetic and measurement (quintal number system, non-standard units), and patterns and logical structures (customary rules, agricultural cycles). Implementation was most effective through Project-Based Learning (PjBL) and Guided Inquiry, which significantly improved students’ ability to devise strategies and validate solutions. The study concludes that integrating Baduy ethnomathematics supports all stages of Polya’s heuristics—understanding the problem, devising a plan, carrying out the plan, and looking back. Its specific contribution lies in providing a cultural cognitive infrastructure that enhances motivation, encourages non-conventional strategies, and facilitates authentic validation. These findings highlight the role of ethnomathematics not merely as contextual enrichment but as a fundamental pedagogical instrument for cultivating critical and creative thinking in mathematics education.